Influence of serum levels of sex hormones on intraocular pressure in menopausal women - TOKER, AYŞE EBRU; ŞAHİN, ÖZLEM (LIPPINCOTT WILLIAMS & WILKINS, 2003)
Purpose: The purpose of this study was to assess the effect that changes in sex hormone levels have on intraocular pressure (IOP) in menopausal women. Subjects and Methods: Thirty menopausal women on hormone replacement therapy and 32 menopausal women who had never received hormone replacement therapy (HRT), matched for age and duration of amenorrhea, participated in this study. Intraocular pressures were measured with Goldmann applanation tonometer. Serum levels were measured for estradiol, free testosterone, and follicle stimulating hormone (FSH). The influence of serum hormone levels on IOP was assessed by correlation analysis. Results: The mean IOP of postmenopausal women receiving HRT (13.29 +/- 2.28 mm Hg) was not significantly different from that of menopausal women not receiving HRT (13.56 +/- 2.5 min Hg, P = 0.24). Higher testosterone levels were associated with higher IOPs in women receiving HRT (r = 0.48, P = 0.02) and in those not receiving HRT (r = 0.42, P = 0.003). No significant correlations were observed between IOP and serum levels of estradiol and FSH in either group. Conclusion: Our data provide evidence for a relation between serum testosterone levels and IOP in menopause. Higher testosterone seems to have a tendency to increase IOP in menopausal women.
Keywords: estradiol; follicle stimulating hormone; free testosterone; hormone replacement therapy; intraocular pressure; menopause; NITRIC-OXIDE SYNTHASE; APPLANATION PRESSURE; AQUEOUS DYNAMICS; OUTFLOW FACILITY; MENSTRUAL-CYCLE; PROGESTERONE; GLAUCOMA; IDENTIFICATION; PREGNANCY; ESTROGEN